The effect of replacing fishmeal with kikuyu leaf meal on the activity of digestive enzymes and growth in Tilapia rendalli, Oreochromis mossambicus and Clarias gariepinus - Hlophe-Ginindza, S. N.; Moyo, N. A. G. (Indian Journal of Animal Research, 2018)
The effect of replacing fishmeal with kikuyu on digestive enzyme activities was investigated in Tilapia rendalli, Oreochromis mossambicus and Clarias gariepinus. Five diets (30% CP: 20 MJ GE kg-1 DM) were formulated. In the control diet, fishmeal was replaced at 25, 50, 75 and 100% by kikuyu leaf meal. Each diet was assigned to three groups of 20 fish (per species). Fish were fed to apparent satiation three times daily for 60 days. There was a significant decrease (P<0.05) in protease, amylase and lipase activities at higher kikuyu inclusion. Protease activities were higher in T. rendalli followed by O. mossambicus and C. gariepinus had the lowest activities. The inability of the fish to produce enough enzymes at higher kikuyu inclusions resulted in significantly lower growth performance and poor protein digestibility. This decrease was more pronounced in C. gariepinus than the tilapias.
Article published in the Indian Journal of Animal Research
Keywords: Amylase; Catfish; Lipase; Protease; Tilapia; Animals-Feeding and Feeds